Checklist of commercially important Scombridae in Aceh, Indonesia - Azzahra Rudi Reefa; Tria Aswina Cut; Ulfa Khaira Nanda; Muhammad Razi Nanda; Muchlisin Zainal A.; Ramadhaniaty Mutia; Riska Rahayu Sri; Damora Adrian; Siti-Azizah Mohd Nor; Fadli Nur (BIO Web of Conferences)
The Scombridae family represents one of the most commercially valuable groups of pelagic fish, widely consumed across the globe. Despite their economic importance and high market demand, scientific data on Scombridae species in Aceh remains scarce. This study aimed to document Scombridae landings from Aceh waters. Fish samples belonging to the Scombridae family were collected from several Fish Landing Sites (TPIs) across Aceh Province. The collected samples were subsequently analyzed at the Genetics and Aquatic Biodiversity Laboratory, Faculty of Marine and Fisheries, Universitas Syiah Kuala. A total of ten Scombridae species were identified from the collected samples: Auxis rochei, Auxis thazard, Euthynnus affinis, Katsuwonus pelamis, Rastrelliger brachysoma, Rastrelliger kanagurta, Scomberomorus commerson, Scomberomorus guttatus, Sarda orientalis, and Thunnus albacares. Banda Aceh had the highest distribution of fish of the Scombridae family, followed by Meulaboh. The findings of this study provide critical baseline data for the future management and conservation of Scombridae fish, particularly in Aceh and Indonesia more broadly.